ANALISIS KEMAMPUAN MEMECAHKAN PERSOALAN ARITMATIKA BERBENTUK VERBAL - Nuraini Sribina (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
This research purpose to determine the ability of studentscompleting the form arithmetic word problem. This researchwas conducted to analyze test results to students 6th gradeelementary school 067774 Medan. The sample selection isdone randomly. The data were analyzed using qualitatifmethod. Wherever in neared is using content analysis.Content analysis is intended to describe the ability of studentsin solving problems in the form of verbal arithmetic.Theresult showed that : the identification of the student answersin solving arithmetic word problem from the aspect ofstudents ability to understand the context of language orverbal problem, compile the relevant models, and drawconclusions contextually still very low. After you know howthe student's ability to solve arithmetic word problem form ofthe fourth aspect of the student's ability is still low, isexpected to allow the reader to take action to minimizemistakes by students while solving the problems of verbalarithmetic shaped so that ability can be improved.